PENGARUH TEKNIK MARMET SEBAGAI BENTUK PEMBERDAYAAN IBU TERHADAP PRODUKSI ASI PADA IBU POST PARTUM: The Effect Of Marmet Techniques As A Form Of Empowerment Of Mothers On Breast Milk Production In Post Partum Mothers - Wahida Yuliana (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2022)
Breast milk (ASI) is the single and best food that meets all the growth and development needs of babies up to 6 months of age as well as foods that are rich in nutrients and are very important for children's growth. Decrease in the amount of milk production in the first days after delivery and the low coverage of exclusive breastfeeding. Some of the things that hinder exclusive breastfeeding include insufficient milk production, working mothers, wanting to be considered modern, problems with the nipples, the effect of advertising on formula milk and the influence of other people, especially family. The purpose of this study was to determine the effect of the marmet technique toward milk production. This type of research is pre-experimental with a pretest and posttest design. The population in this study were 30 post partum mothers with a total sample of 17 respondents who met the inclusion criteria with the Simple Random Sampling technique. The instrument in this study used SOP (standard operating procedures) observation sheets. This research has been conducted and analyzed by paired sample t test. The results of this study indicate the effect of the marmet technique on breast milk production with p = 0.001